RLC Circuits to change the shape of electromagnetic signals - Alizoti, Alion (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This paper introduces a research work concerning electromagnetic signals. The research has been going on for several years now, focusing mainly on developingsuccessful publicattempts to produce electromagnetic signals, and also altering them efficiently. Following notable footsteps onthe history of electromagnetic evolution, the research is based on both theoretical approaches and practical experiments. Thence, affirmative conclusions about electromagnetic signals denote that, the application of RLC circuits is a good simple method to produce electromagnetic signals and, also, change some of their features, such as amplitude, frequency, or shape. Aspects of this research are introducedto class activities with regard to proper curriculum recommendations and further issued with presentationsto advanced international events.